Strengthening legal awareness and digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in Sindang Laya village - Upi Parida; Patra Bethania Panjaitan; Padma Nurdin; Gilang Baghdad (Science Center Group, 2026)
Background: Micro, Small, and Medium Enterprises (MSMEs) play an essential role in supporting local economic resilience, employment, and community welfare. However, many rural MSMEs still face barriers related to limited legal awareness, incomplete business legality, low digital literacy, and restricted access to digital business platforms. Strengthening business legality and digital transformation is therefore important to improve MSME competitiveness, consumer trust, and business sustainability. Objective: This study aimed to describe the implementation and outcomes of a community-based program for strengthening legal awareness and digital transformation among MSME actors in Sindang Laya Village. Methods: This community service program used a participatory empowerment approach through socialization, training, mediation, and direct mentoring. The activity was conducted on 13 January 2026 at the Sindang Laya Village Hall, Cinangka Subdistrict, Serang Regency, Banten Province, Indonesia. The program involved university facilitators, students, the village government, and MSME actors. The intervention included education on business legality, introduction to the Business Identification Number or Nomor Induk Berusaha (NIB), guidance on the Online Single Submission system, introduction to QRIS as a digital payment system, and assistance with business location registration through Google Maps. Program outcomes were assessed based on participant engagement, increased understanding, initiation of business legality processes, and adoption of digital business tools. Results: The program improved MSME actors’ understanding of the importance of business legality and digital transformation. Some participants successfully obtained or initiated the process of obtaining NIB after receiving direct assistance. MSME actors also began to understand the use of QRIS as a digital payment method and registered or prepared their business locations through Google Maps to improve business visibility. The involvement of the village government, university team, and students supported an integrated and collaborative empowerment process. Conclusion: The integration of legal education, digital training, mediation, and participatory mentoring strengthened MSME readiness for formalization and digital business adaptation in Sindang Laya Village. Continuous mentoring is needed to sustain business legality, optimize digital payment use, and improve MSME competitiveness.